Factors Causing The Problem Of Not Disposing Of Garbage In Its Place In The Upi Cibiru Canteen - Puspitasari, Regita; Faridah , Tsana Nur; Nurjaman , Asep Rudi (CV. Generasi Insan Rafflesia, 2023)
This mini research study aims to find out the factors that cause the problem of not throwing garbage in its place in the canteen of the University of Indonesia Education Cibiru Campus. This mini research research uses a qualitative approach method, namely literature study or literature study as well as conducting observations and interviews with students of the University of Indonesia Education Cibiru Campus. After conducting mini research research, four factors were obtained that caused the problem of not throwing garbage in its place in the canteen of the University of Indonesia Education Cibiru Campus, one of which was the lack of student awareness. Therefore, a solution is needed to solve this problem, one of which is by holding socialization.